2014
DOI: 10.1371/journal.pone.0094047
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Host Plant Choice and Larval Performance in Bactericera cockerelli

Abstract: Among the many topics of interest to ecologists studying associations between phytophagous insects and their host plants are the influence of natal host plant on future oviposition decisions and the mechanisms of generalist versus specialist host selection behavior. In this study, we examined the oviposition preferences, behavior and larval development of the tomato/potato psyllid, Bactericera cockerelli. By rearing psyllids with two distinct geographically-linked haplotypes on different host plants, we were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…The haplotypes did differ in development rates on species allowing development, with psyllids of the Central haplotype developing more rapidly than psyllids of the Northwestern haplotype. Other studies have shown that haplotypes of potato psyllid differ in biological traits, including settling and oviposition behavior [68], development rates [25], body size [24, 25], and composition of endosymbiont communities [27]. The Central haplotype developed more rapidly on cultivated and weedy Solanaceae than psyllids of the Northwestern haplotype [25], which is consistent with our observations.…”
Section: Discussionsupporting
confidence: 91%
“…The haplotypes did differ in development rates on species allowing development, with psyllids of the Central haplotype developing more rapidly than psyllids of the Northwestern haplotype. Other studies have shown that haplotypes of potato psyllid differ in biological traits, including settling and oviposition behavior [68], development rates [25], body size [24, 25], and composition of endosymbiont communities [27]. The Central haplotype developed more rapidly on cultivated and weedy Solanaceae than psyllids of the Northwestern haplotype [25], which is consistent with our observations.…”
Section: Discussionsupporting
confidence: 91%
“…Some authors support strongly the performancepreference hypothesis, predicting that females will maximize chances of success for their offspring by choosing those host plants for oviposition on which their larvae perform best (Jaenike, 1978;Gripenberg et al, 2010). Other authors argue instead that females do not always lay eggs on the plant species on which their offspring grows and survives, and on which their performance is best (Prager et al, 2014;Konig et al, 2016). Several explanations for such a lack of positive correlation between oviposition preference and larval growth performance have been suggested: for example, the rarity of the optimal host plant (Wicklund & Friberg, 2009), or the fact that egg-laying females could be oriented to maximize their performance, rather than that of their progeny (Mayhew, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the influence of odor substances during preimaginal stages might be linked to an intimate contact with such substances, like feeding on it. Indeed, several adult holometabolous insects shows a strong preference for oviposit on plants at which they fed during their larval stages (Blackiston et al 2008;Anderson et al 2013;Prager et al 2014), showing that there is associative learning during larval stages.…”
Section: Discussionmentioning
confidence: 99%